Semua Orang Dipilih-Nya Dari Semula: Eksegese Kitab Roma 8:28-30 - Hibur Wanti Mattu (KAMASEAN: Jurnal Teologi Kristen, 2020)
In Romans 8: 28-30 it states that God chose. This arises the mistaken understanding that if God has chosen from the beginning, then there are those who are chosen and those who are not. Then, how does God's understanding choose people from the beginning? If so, are the good deeds of the believer still relevant? does the Great Commission still apply to believers? Therefore, the purpose of this writing is to seek the meaning of all the people He chose from the beginning in Romans 8: 28-30. This writing uses a qualitative writing method with a type of exegesis approach, namely Grammatical-context study. Grammatical means to examine the phrase all the people He chose from the beginning in Romans 8: 28-30. The intended context analysis is to link each analyzed word to the context in which the word is located. The findings of this writing which are related to being chosen in the Book of Romans are that the election of God from the beginning was an act of God long before all were made who knew humans and chose who would receive Christ and His glory. This calling occurs according to and based on God's purpose. God's call for believers is for a certain purpose or plan. The call is for believers to be like Christ and share in His glory and contribute well to God's plan. The purpose of the call is to accept the justification of the mistakes and sins that have been done. All sins and mistakes will be blotted out by the blood of Jesus, as a justification for His death, and His resurrection that has sacrificed for those who believe in Him. The Last is glorified. This is God's future action where He frees believers from every aspect of sin, at His second coming. This process requires all believers to be like Jesus Christ. Dalam Kitab Roma 8:28-30 menyatakan tentang Allah memilih. Hal ini muncul pemahaman yang keliru bahwa jika Allah telah memilih dari semula, maka ada yang terpilih dan ada yang tidak terpilih. Lalu, bagaimana pemahaman tentang Allah memilih orang-orang dari semula? Jika demikian, apakah perbuatan baik orang percaya masih relevan? apakah amanat agung masih berlaku bagi orang percaya? oleh karena itu, tujuan penulisan ini adalah untuk mencari makna semua orang dipilih-Nya dari semula dalam kitab Roma 8:28-30. Penulisan ini menggunakan metode penulisan kualitatif dengan jenis pendekatan eksegese yakni kajian gramatikal-konteks. Gramatikal maksudnya adalah mengkaji frasa semua orang dipilih-Nya dari semula dalam kitab Roma 8:28-30. Analisa konteks yang dimaksudkan adalah menghubungkan setiap kata yang dianalisa terhadap konteks di mana kata itu berada. Temuan-temuan dari penulisan ini yang terkait dengan dipilih dalam kitab Roma adalah bahwa pemilihan Allah dari semula merupakan suatu tindakan Allah jauh sebelum semuanya dijadikan yang telah mengenal manusia dan memilih siapa yang akan menerima Kristus dan kemuliaanNya. Panggilan ini terjadi sesuai dengan dan berdasarkan tujuan Allah. Panggilan Allah bagi orang-orang percaya adalah untuk tujuan atau rencana tertentu. Panggilan tersebut agar orang percaya menjadi serupa seperti Kristus dan ikut ambil bagian dalam kemuliaan-Nya, dan berkontribusi baik dalam rencana Allah. Maksud panggilan itu adalah menerima pembenaran dari kesalahan-kesalahan dan dosa yang telah diperbuat. Segala dosa dan kesalahan akan dihapuskan oleh darah Yesus, sebagai pembenaran atas kematianNya, dan kebangkitanNya yang telah berkorban bagi mereka yang percaya kepadaNya. Terakhir dimuliakan. Ini adalah tindakan Allah di masa depan di mana Ia membebaskan orang percaya dari setiap aspek dosa, pada kedatangan-Nya kedua kali. Proses ini menuntut semua orang percaya untuk serupa dengan Yesus Kristus.